(untitled) (Informatica, 2016)
Recently, using third party data centers has become a popular choice for storing enter- prise data and deploying services. The fast growth of data centers in size and in number makes them become huge energy consumption points. Up to 70% of energy consump- tion is due to server running and cooling. In order to reduce energy consumption, recent researches have proposed turning off certain switches in data centers with little traffic flow. However, when those switches are turned off, the data center becomes vulnerable to failures due to low connectivity between servers. In order to overcome this weakness, this paper proposes to use path protection to ensure that all connections in the data center retain survivability upon any single failure. The paper also proposes an algorithm to calculate a tailored topology for the data center so that unnecessary switches can still be turned off. The simulation results show that the proposed solution makes data cen- ters survivable while still saving energy significantly, mostly in big size data centers.